Multiplexed CRISPR/Cas9-Mediated Knockout of Laccase Genes in Salvia miltiorrhiza Revealed Their Roles in Growth, Development, and Metabolism - Zhou, Zheng; Li, Qing; Xiao, Liang; Wang, Yun; Feng, Jingxian; Bu, Qitao; Xiao, Ying; Hao, Kai; Guo, Meili; Chen, Wansheng; Zhang, Lei (Frontiers in Plant Science, 2021)
Laccases are multicopper-containing glycoproteins related to monolignol oxidation and polymerization. These properties indicate that laccases may be involved in the formation of important medicinal phenolic acid compounds in Salvia miltiorrhiza such as salvianolic acid B, which is used for cardiovascular disease treatment. To date, 29 laccases have been found in S. miltiorrhiza(SmLACs), and some of which (SmLAC7 and SmLAC20) have been reported to influence the synthesis of phenolic acids. Because of the functional redundancy of laccase genes, their roles in S. miltiorrhiza are poorly understood. In this study, the CRISPR/Cas9 system was used for targeting conserved domains to knock out multiple genes of laccase family in S. miltiorrhiza. The expressions of target laccase genes as well as the phenolic acid biosynthesis key genes decrease dramatically in editing lines. Additionally, the growth and development of hairy roots was significantly retarded in the gene-edited lines. The cross-sections examination of laccase mutant hairy roots showed that the root development was abnormal and the xylem cells in the edited lines became larger and looser than those in the wild type. Additionally, the accumulation of rosmarinic acid as well as salvianolic acid B was decreased, and the lignin content was nearly undetectable. It suggested that SmLACs play key roles in development and lignin formation in the root of S. miltiorrhiza and they are necessary for phenolic acids biosynthesis.